Dissipative Generation of Two‐Mode Mechanical Squeezing via Frequency Modulation. Issue 2 (17th December 2021) - Zhang, Tian‐Qi; Wang, Dong‐Yang; Bai, Cheng‐Hua; Zhang, Shou; Wang, Hong‐Fu
Abstract: Different from the general schemes of two‐mode mechanical squeezing, a dissipative scheme to generate strong and robust two‐mode mechanical squeezing via frequency modulation of cavity modes in a cavity optomechanical system consisting of a modulated two‐mode optical cavity and two mechanical oscillators is proposed. It is shown that the 20 dB 20dB strong mechanical squeezing, which is highly robust against the thermal noise, can be engineered by means of cavity dissipation. Moreover, the squeezing mechanism is explored via analytical approach and it is found that the squeezing direction is controlled by modulation amplitude. The scheme provides an alternative pathway to generate strong mechanical–mechanical entanglement. Abstract : In this article, a dissipative scheme is proposed to generate strong and robust two‐mode mechanical squeezing via frequency modulation of cavity modes in a cavity optomechanical system. The 20 dB strong mechanical squeezing, which is highly robust against the thermal noise, can be engineered by means of cavity dissipation. Further numerical simulations show that the squeezing direction is controlled by modulation amplitude.